Light-Dependent Activation of the GCN2 Kinase Under Cold and Salt Stress Is Mediated by the Photosynthetic Status of the Chloroplast - Lokdarshi, Ansul; Morgan, Philip W.; Franks, Michelle; Emert, Zoe; Emanuel, Catherine; von Arnim, Albrecht G. (Frontiers in Plant Science, 2020)
Regulation of cytosolic mRNA translation is a key node for rapid adaptation to environmental stress conditions. In yeast and animals, phosphorylation of the -subunit of eukaryotic translation initiation factor eIF2 is the most thoroughly characterized event in regulating global translation under stress. In plants, the GCN2 kinase (General Control Non-derepressible-2), is the only known kinase for eIF2. GCN2 is activated under a variety of stresses including reactive oxygen species. Here we provide new evidence that the GCN2 kinase in Arabidopsis is also activated rapidly and in a light dependent manner by cold and salt treatments. These treatments alone did not repress global mRNA ribosome loading in a major way. The activation of GCN2 was attenuated by inhibitors of photosynthesis and antioxidants, suggesting that it is gated by the redox poise or the reactive oxygen status of the chloroplast. In keeping with these results, gcn2 mutant seedlings were more sensitive than wild type to both cold and salt in a root elongation assay. These data suggest that cold and salt stress may both affect the status of the cytosolic translation apparatus via the conserved GCN2-eIF2 module. The potential role of the GCN2 kinase pathway in the global repression of translation under abiotic stress will be discussed.